IPMK modulates hepatic glucose production and insulin signaling. Issue 8 (13th July 2022) - Jung, Ik‐Rak; Anokye‐Danso, Frederick; Jin, Sunghee; Ahima, Rexford S.; Kim, Sangwon F.
Abstract: Hepatic glucose production (HGP) is crucial for the maintenance of normal glucose homeostasis. Although hepatic insulin resistance contributes to excessive glucose production, its mechanism is not well understood. Here, we show that inositol polyphosphate multikinase (IPMK), a key enzyme in inositol polyphosphate biosynthesis, plays a role in regulating hepatic insulin signaling and gluconeogenesis both in vitro and in vivo. IPMK‐deficient hepatocytes exhibit decreased insulin‐induced activation of Akt‐FoxO1 signaling. The expression of messenger RNA levels of phosphoenolpyruvate carboxykinase 1 (Pck1) and glucose 6‐phosphatase (G6pc), key enzymes mediating gluconeogenesis, are increased in IPMK‐deficient hepatocytes compared to wild type hepatocytes. Importantly, re‐expressing IPMK restores insulin sensitivity and alleviates glucose production in IPMK‐deficient hepatocytes. Moreover, hepatocyte‐specific IPMK deletion exacerbates hyperglycemia and insulin sensitivity in mice fed a high‐fat diet, accompanied by an increase in HGP during pyruvate tolerance test and reduction in Akt phosphorylation in IPMK deficient liver. Our results demonstrate that IPMK mediates insulin signaling and gluconeogenesis and may be potentially targeted for treatment of diabetes. Graphical abstract: